Background Checks for all Gun Buyers and Gun Violence Restraining Orders: State Efforts to Keep Guns from High-Risk Persons. Issue 1 (2017) - Vernick, Jon S.; Alcorn, Ted; Horwitz, Joshua
Abstract : There were more than 36, 000 firearm-related deaths in the U.S. in 2015. Under federal law, a background check is required only for gun purchases from licensed dealers. Research suggests that some persons prohibited from owning a gun turn to private sellers, including those identified online, to attempt to obtain a firearm. State-level approaches to make it more difficult for high-risk persons to purchase or possess firearms include universal background check (UBC) and gun violence restraining order (GVRO) laws. UBC laws, on the books in 18 states as of the end of 2016, can reduce both homicide and suicide rates. After Colorado adopted a UBC law in 2013, the number of background checks conducted by private sellers for sales occurring at places other than gun shows steadily increased. GVRO laws give law enforcement and families the authority to petition a court to temporarily remove firearms from an individual who presents a danger to himself or others during times of crisis, regardless of whether that person has been diagnosed with a mental illness. California enacted a GVRO law in 2014. Data are emerging to suggest the effectiveness of GVRO-type laws at averting suicides and providing an entryway to services.